Experimental study of stainless steel channel-to-plate connections under tension - May, Soe Kyaw (Nanyang Technological University, 2021)
Experimental study of austenitic stainless steel channel-to-plate connections has been conducted and presented in this report. The experimental tests of sixteen specimens with various configurations which were fabricated from grade 304 austenitic stainless steel are reported. The experimental programme in this project consisted of material tensile coupon tests and connection tests. The geometric factors affecting the ultimate tensile strength capacity of the austenitic stainless steel channel-to-plate connections were studied by analysing the obtained test results. Moreover, the test results were used to conduct an accuracy assessment of two current design standards – European code and American specification. It was found that the European code provides conservative capacity predictions, while the American specification offers more accurate capacity predictions.